Microsoft 70-484 : essentials of developing Windows Store apps using C# - Roach, Brian E.; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"Our Essentials of Developing Windows Store Apps Using C# course provides developers with the knowledge and decision making skills for utilizing C# and Microsoft Visual Studio 2012 to develop and design Windows store apps, create user interfaces, and manage security and data. This course provides credit towards the MCSD certification. This course is designed for developers with two to five years of experience with C# and XAML applications, as well as experience with developing applications in accordance with Windows Store app guidelines."--Resource description page.
Presenter, Brian E. Roach.
Title and publication information from resource description page (Safari, viewed June 8, 2017).
Presenter's name from title screen (Safari, viewed June 8, 2017).
Keywords: Windows (Computer programs) -- Examinations -- Study guides; C# (Computer program language) -- Examinations -- Study guides; Application software -- Development -- Examinations -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Electronic books